2022
DOI: 10.3390/foods11192936
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Ginsenoside Rg3, Compound K, and Antioxidant Activity of Cultivated Wild Panax Ginseng (CWPG) by Puffing

Abstract: Cultivated wild Panax ginseng (CWPG) has been reported to have a higher content of ginsenoside than normal Panax ginseng. This study was carried out to increase the antioxidant activity and active ingredients by the puffing process. Therefore, effects of moisture content and pressure conditions on the antioxidant activity and active ingredients of CWPG were investigated. Extraction yield and crude saponin content were decreased at all moisture contents with increasing pressure. HPLC analysis showed that the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…These results were attributable to the formation of porous structure and the chemical bond-breaking by the puffing process [6], and could be explained by the increase in certain substances such as maltol, a Maillard reaction, and the increase in dissolution rate of antioxidants after puffing [36][37][38]. Similarly, it has been reported that TFC, TPC, and DPPH radical scavenging capacity in wild Panax ginseng were increased by puffing [5]. The decrease or no change in TFC, TPC, and DPPH radical scavenging capacity after HHP could be attributed to the decrease in the extraction yield.…”
Section: Functional Propertiesmentioning
confidence: 92%
See 2 more Smart Citations
“…These results were attributable to the formation of porous structure and the chemical bond-breaking by the puffing process [6], and could be explained by the increase in certain substances such as maltol, a Maillard reaction, and the increase in dissolution rate of antioxidants after puffing [36][37][38]. Similarly, it has been reported that TFC, TPC, and DPPH radical scavenging capacity in wild Panax ginseng were increased by puffing [5]. The decrease or no change in TFC, TPC, and DPPH radical scavenging capacity after HHP could be attributed to the decrease in the extraction yield.…”
Section: Functional Propertiesmentioning
confidence: 92%
“…P-MCPG and H-MCPG showed a 5.29% and 11.31% increase, respectively. Puffing treatments have been reported to increase the dissolution rate of the internal components by destroying the cell wall and forming a porous structure [5,6,20]. In addition, HHP treatments have been reported to increase the mass transfer rate by destroying the cell wall [27].…”
Section: Extraction Yield and Crude Saponin Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…As, minor ginsenoside C-K is a precursor compound of 3-oxo-C-K [17] that can effectively decrease the UVB-induced side reaction [45], antioxidant ability [24], and resist free radicals that cause skin photoaging [24]. Therefore, the efficacy of 3-oxo-C-K was screened out for the ultraviolet irradiated human fibroblast cell.…”
Section: Effect Of C-k and 3-oxo-c-k On The Synthesis Of Mmp-1 And Pr...mentioning
confidence: 99%
“…Thus, very low or very high pH values effect in broad loss of enzymatic activity. Therefore, the effect of pH on the activity of HSDLb1 was evaluated using 5.0 mM C-K as a substrate in 20 mM of different buffers solutions [KCl-HCl and glycine-HCl for pH 2-3, sodium acetate and sodium phosphate (pH 4.0-7.5), Tris-HCl (pH 8.0, and 10.0), and Tris-NaOH (pH 12.0)] for 24 h. To examine the effect of temperature on HSDLb1 activity the samples were kept at the optimum pH value for 24 h in 100 mM potassium phosphate buffer containing 5.0 mM C-K at various temperature (20,25,30,37,40,45,50,55, and 60 • C) for 24 h. After 24 h, the samples were collected and HSDLb1 enzymatic activity was identified. Additionally, the effects of metal ions on the activity of HSDLb1 were also identified.…”
Section: Effect Of Different Ph Temperature and Metal Ionsmentioning
confidence: 99%